Prototypen - Schemata - Konstruktionen Untersuchungen zur deutschen Morphologie und Syntax - Binanzer, Anja; Gamper, Jana; Wecker, Verena (Reihe Germanistische Linguistik, 2021)
Prototype, schema and construction are three central concepts that can be used to model mental representations of grammatical structures and relations within the frame of functional-cognitive grammar theories. This volume reviews these concepts using new linguistics analyses of the morphology and syntax of the German language from applied disciplines, taking into consideration a wide methodological spectrum.